PENGARUH PROSES SELEKSI KARYAWAN DAN LINGKUNGAN KERJA FISIK TERHADAP MOTIVASI KARYAWAN PADA PT BANK MANDIRI PERSERO CABANG INDARUNG PADANG - Muliawati, Rani; Masrin, Indra; Eka Putri, Yosi (Pendidikan Ekonomi, 2014)
ABSTRACT                 This research did in Bank Mandiri Branch Indarung Padang on January 2014. The aim of  the research are to know the influence of employee selection and the environment. Of physical work foward employee motivation.                 The technigue of data collection used multiple regression linear analysis with SPSS 16. There wewe 34 respondent in this reserch as a sample and the technigues which is used to get it use Total Sampling technigue.                The result of test showed all independence variable had positive influence to the employee with 0,615 for motivation and o,566 for physical environment, the point that the researcher in Bank Mandiri are influenced by the selection and the environment of physical work.                Based on the result of the research, the most influential factor for motivation in Mandiri Bank is the selection of employee variable it means, the selection of the employee have to be better and important, specifically for personal interview. An employee must be ready  to challenged, have good motivation and attitude, honest, and capable in teamwork.